2014
DOI: 10.1063/1.4900929
|View full text |Cite
|
Sign up to set email alerts
|

Giant self-biased converse magnetoelectric effect in multiferroic heterostructure with single-phase magnetostrictive materials

Abstract: Giant self-biased converse magnetoelectric (CME) effects with obvious hysteretic behaviors are systematically investigated in two-phase SmFe2/PZT [Pb(Zr1−x, Tix)O3] multiferroic laminates at room temperature. Taking advantage of the huge anisotropic field of SmFe2 plate, large remnant CME coupling is provoked by this field instead of permanent magnets to bias the laminate. Consequently, bitable magnetization status switching is realized through a smaller ac voltage far below the electric coercive field in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…In the absence of H dc a maximum a CME of 5 (mG cm)/V is achieved at B 1 mode. This is three orders of magnitude higher than the previously reported self-biased CME coefficient in laminate composite [19]. The R 1 mode and B 2 mode shows a self-biased a CME value of 1.8 and 1.2 (mG cm)/V respectively.…”
Section: Resonance Me Studiescontrasting
confidence: 47%
See 1 more Smart Citation
“…In the absence of H dc a maximum a CME of 5 (mG cm)/V is achieved at B 1 mode. This is three orders of magnitude higher than the previously reported self-biased CME coefficient in laminate composite [19]. The R 1 mode and B 2 mode shows a self-biased a CME value of 1.8 and 1.2 (mG cm)/V respectively.…”
Section: Resonance Me Studiescontrasting
confidence: 47%
“…The hysteresis and remanent magnetization in the ferromagnetic layer of the ME composite give rise to ME coefficient in the absence of external bias field in these structures. But there are only very few studies on self-biased CME effect and the reported values are low [14,19].…”
Section: Introductionmentioning
confidence: 98%
“…These values correspond to a remanent magnetoelectric coupling at zero bias field µ 0 H, which is related to the hysteretic magnetic behavior and the strong remanent magnetization [49,71]. This is truly encouraging for the dynamic CME self-biased potential of FeGa/PMN-PZT in applications, which is revealed in measurements that assess the magnetization change under an alternating AC electric field superimposed to a DC magnetic bias field µ 0 H (yielding a non-zero remanent CME(µ 0 H) at µ 0 H = 0) [31,[67][68][69].…”
Section: Magnetoelectric Coefficient α Cmementioning
confidence: 66%
“…FeGa has been the choice of magnetostrictive material for many studies, suggesting versatile proposals for the development of multifunctional devices exploiting both DME [56][57][58] and CME effects [9,19,24,[59][60][61][62][63][64][65][66]. Among these studies some have reported the dynamic self-biased effect, also called remanent CME, which is a desirable property recently seeked to control the magnetization using an electric field in ME devices without the need for the assistance of an external biasing magnetic field [31,49,[67][68][69][70][71]. Self-biased CME is indeed important for lower-energy consumption and more compact ME devices.…”
Section: Introductionmentioning
confidence: 99%
“…The device concepts that have recently emerged using electric field control of magnetization switching provide an alternative route to achieve fast and high-density information storage with very low energy consumption . A multiferroic heterostructure composed of FM and ferroelectric (FE) materials is well-suited for high-speed, low-power, and ultradense device structures. So far, there have been three main methods available for the electric field control of magnetism in FM/FE multiferroic heterostructures, including (i) strain-mediated magnetoelastic coupling with the piezostrain of the FE transferred to the FM layer, , (ii) exchange bias-mediated interaction, , and (iii) manipulation of charge carrier density. , Among them, the electric field control of magnetism through strain-mediated coupling in FM/FE multiferroic heterostructures has become a hot topic due to the availability of a variety of room-temperature FM and FE materials and the remarkable magnetoelectric effects . The strain is induced by applying an electric field to the FE layer via the piezoelectric effect, and the induced strain is then transferred to the FM layer, altering the magnetization via magnetostriction.…”
mentioning
confidence: 99%